DINAMIKA PERKREDITAN DI PRIANGAN 1900-1942 - Sri Ana Handayani (Indonesian Journal of Dialectics, 2012)
The present research examines the dynamics of credits in Priangan (1900-1942). The major issues to be addressed here are the matter of credit necessity for the farmers of Priangan, the background and considerations for the Netherland Indies government to reform the traditional credit system, the response of the inhabitants to the formal credit, and the impacts of the change in credit systems on the Priangan society.As a historical research, the present study employs historical method embracing four major working stages: heuristics, criticisms, interpretation, and historiography. To analyze the patterns of economic behaviour of Priangan society concerning credits, “Economic Behavior Pattern” approach introduced by Karl Polanyi and “Social Action” approach by Weber are jointly used.Before the credit reform was put into effect by the Dutch colonial government, the credit loans took the forms of merchandise selling and buying on the installment plan travelling through villages (mindring), land lease and mortgage (sewa dan gadai tanah), and practice of selling and buying agricultural product long before the harvest (ijon). After the reform, credit loans were channeled through village barn (lumbung desa), village bank (bank desa), and people bank (bank rakyat). The main conclusion drawn from the research is that the Priangan society was able to creatively adapt to the formal credit system introduced by the colonial government. Based on their local wisdoms, the Priangan people could create a credit institution, which suited to the their own characteristics, namely cooperative productive credit supported by socio-cultural, economic, and political structures. The new credit system had formed the pattern of dynamic economic behaviour nurturing entrepreneurial spirits among the Priangan society.